Evaluating Interactive Murals: An Empirical Study on Teaching Basic Vocabulary to Young Children - Yuliani, Sri; Mardatillah, Annisa; Linarta, Arie (International Journal of Language Education, 2025)
This empirical study evaluates the effectiveness of interactive murals in teaching basic vocabularies to young children. The study is grounded in educational theories that emphasize active engagement, multisensory learning, and social interaction as critical components of effective early childhood education. The primary objectives of this study are to evaluate the impact of interactive murals on vocabulary retention among young children, assess the levels of engagement and motivation associated with the use of interactive murals compared to traditional teaching methods, and gather teachers' perspectives on the implementation and effectiveness of interactive murals in the classroom. Experimental research method design employed quantitative data to provide a comprehensive evaluation. Pre-tests and post-tests were administered to measure vocabulary retention. The quantitative analysis revealed that the experimental group showed significantly greater improvement in vocabulary retention compared to the control group. The results highlight the need for schools to invest in innovative educational tools and provide professional development for teachers. Future research should explore the long-term impacts of interactive murals and address the technological challenges associated with their use.